Jane Austen and the romantic poets - Deresiewicz, William, 1964- (Columbia University Press, 2004)
This elegant and thoughtful work offers an important new way of understanding Jane Austen by defining the fundamental impact and influence of British Romanticism on her later novels. In comparing the earlier and later phases of Austen's career, Deresiewicz addresses an important yet neglected issue regarding her work: the longstanding critical consensus that Austen's last three novels (Mansfield Park, Emma, and Persuasion) represent far greater artistic achievements than do her first three (Northanger Abbey, Sense and Sensibility, and Pride and Prejudice). Jane Austen and the Roman.
Keywords: Austen, Jane, -- 1775-1817 -- Knowledge -- Literature.; Austen, Jane, -- 1775-1817 -- Criticism and interpretation.; Austen, Jane, -- 1775-1817; English poetry -- 19th century -- History and criticism.; Influence (Literary, artistic, etc.) -- History -- 19th century.; Romanticism -- Great Britain.; Poésie anglaise -- 19e siècle -- Histoire et critique.; Influence littéraire, artistique, etc. -- Histoire -- 19e siècle.; Romantisme -- Grande-Bretagne.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- European -- General.; Literature; English poetry; Influence (Literary, artistic, etc.); Romanticism; Great Britain; 1800-1899; Criticism, interpretation, etc.; History